THE EFFECT OF SOCIALIZATION, TAX EXAMINATION AND TAX COLLECTION ON PPH AT KPP PRATAMA MEDAN PETISAH - Sari, Ayu Kurnia; Saputra, Hendra; Ramadhani, Ulpa (Accounting and Business Journal, 2020)
This study aims to carry out tax socialization activities, tax audits and tax collection actions to affect income tax revenue at KPP Pratama Medan Petisah. Tax outreach activities are measured by the number of socialization activities held by KPP Pratama Medan Petisah for individual taxpayers. Tax audits are measured from SKP, namely the number of SKPKB and SKPKBT issued by KPP Pratama Medan Petisah per month from 2015 to 2017. Income tax revenue is the amount of income tax installments of Article 25 individual taxpayers at KPP Pratama Medan Petisah and tax collection actions are measured based on the number of forced letters issued by KPP Pratama Medan Petisah per month from 2015 to 2017. This research uses quantitative data in the form of secondary data obtained from KPP Pratama Medan Petisah for the fiscal year 2015 to 2017. The data analysis technique used is linear regression. multiple. This study proves that the tax socialization, tax audit and tax collection activities together have an effect on income tax revenue at KPP Pratama Medan Petisah. Partial testing concludes that socialization and tax audit activities have a positive effect on income tax revenue at KPP Pratama Medan Petisah. Meanwhile, the tax collection action variable has no effect on income revenue at KPP Pratama Medan Petisah.